Proposta de um instrumento para diagnóstico da gestão da inforação e do conhecimento (GIC) de forma integrada para bibliotecas universitárias. - Silva, Adriana Nóbrega da (2013)
This research is intended to search for Information Management and Knowledge Management (IKM) for construction of an integrated diagnostic tool GIC in university libraries, based on the strategic management of the institution. The focus of this research is the understanding of Knowledge Management (KM) and its systematization as a process as is the Information Management (IM), and the integration of both into a model that allows the diagnosis. The research was conducted at the Federal University of Ceará (UFC) and the University of Fortaleza (UNIFOR). The research aims to propose a main instrument to diagnose the management of information and knowledge (GIC) in an integrated way to university libraries. This is an exploratory and descriptive qualitative, case study considered. It adopts content analysis to collect, organize and analyze data. The survey results indicated that there is need to expand discussions about Information Management and Knowledge directed at university libraries, exploring in depth the specific issues of GIC, such as the valuation of intellectual capital in the university library, analyzes librarians directors and managers, understanding that the whole process of Information Management and Knowledge depends on thoughtful actions, aligned with organizational expectations and users, making use of human, material and technological resources available also present that human knowledge in the university library arises from human interaction, facilitated by emerging technological devices. In the information system of the university library, they become increasingly using various information retrieval systems, networks enhanced by the use of remote communication. Thus, the libraries not only benefit from optimizing the management of traditional library resources. Social networks are present, facilitating communication between library staff, and between them and the users, converging information services more convenient and efficient. In modern times, the IG and CG expand the relevance of the role of the librarian, which is not restricted to the mere management of documentary information. He becomes a central character in the administration of the library, whose skills go beyond the rationality of technical librarian, to meet people (users / customers and employees).